Bioinspired Robust Mechanical Properties for Advanced Materials. Issue 9 (14th September 2022) - Wijerathne, Binodhya; Liao, Ting; Ostrikov, Kostya (Ken); Sun, Ziqi
Abstract : Bioinspired Materials In article number 2100228, Ziqi Sun and co‐workers review the recent progress in designing artificial advanced materials with robust mechanical properties by learning from the biological structures possessing exceptional strength, toughness, sharpness, rigidity, resilience, and tolerance. These understandings on the extraordinary natural structures and the bioinspired materials are expected to provide further insights into designing novel materials and composites.